PENGARUH SERTIFIKASI KOMPETENSI TERHADAP KINERJA PERUSAHAAN DI PT. PLN (PERSERO) ULTG KOLAKA - Iksan, Iksan; Asriany, Asriany; Halim, Ibrahim (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to find out how competency certification has an impact on company performance at PT. PLN (Persero) Kolaka Substation Smelter. This study uses a quantitative approach with data collection through questionnaires. The data were analyzed using simple linear regression. This study involved 27 people. The results of the analysis show that the regression coefficient shows a positive relationship between competence and business performance. With a significance value well below the threshold, competency certification has a significant influence on a company's performance, according to a partial test. In addition, the analysis of the F test shows that the regression model is significant overall, indicating that competency certification has a significant influence on the performance of the company simultaneously. Therefore, the company's performance at the Kolaka Smelter Substation PT. PLN (Persero) is greatly influenced by competency certification. Keywords : Competency, Performance Certification.